Low-frequency electric fields at smartphone surface - John Voccio; Andrew Seredinski; Jiahui Song; Ali Khabari; Marina Chuery; Hunter Oshman; Patricia Sadde Mujica (AIP Advances, 2023)
Mobile phones, tablets, and other devices with capacitive touchscreens are ubiquitous in modern society. Consequently, the battery health of such devices along with the potential public health impacts of their typical use is of high importance. Here, we investigate the AC electric field present near the touchscreen surface during device charging. Using a Trifield TF2 meter for magnitude and a Faraday pickup coil for frequency, we study the AC electric field at the surface of an Apple iPhone 8 mobile phone in the 0–200 kHz range, well below the uplink/downlink bands used for cellular signals. We find the addition of the frequency content throughout this range and with integrated magnitude of the order of 500 V/m rms under certain phone charging conditions. Our findings suggest that the field is being generated by the lithium-ion battery. We note also that these AC electric fields are not present when the device is charged from a portable power bank.